Comparison Between Equations Obtained by Means of Multiple Linear Regression and Genetic Programming to Approach Measured Climatic Data in a River - Arganis, M.L.; Val, R.; Domínguez, R.; Rodríguez, K.; Dolz, J.; Eaton, J.M. (IntechOpen, 2012)
None